Science Teachers' Communication Behavior, Lesson Preparation, and Examination System - Mae Galorport (Philippine Association of Institutions for Research, Inc., 2014)
Science teachers are facilitators of students' learning. This study investigated the teaching behavior of science teachers in their science classroom as assessed by the college students taking Science subjects in Bukidnon State University, Philippines. Specifically, it sought to determine the science teachers' teaching behavior in the following aspects: 1) Communication Behavior; 2)Lesson Preparation; and 3) Examination System; and identify an action plan that could be suggested means to strengthen the professional development of biological and physical science teachers. The study employed both quantitative and qualitative methods of research. A questionnaire developed by the researcher and the adviser to survey the science teachers' teaching behavior and focus group discussion were used to affirm students' responses and assess other science teachers' teaching behaviors that were not mentioned in the questionnaire. Results showed that college students strongly agree that their science teachers practiced communication behavior at all times. Likewise, the students agreed that their science teachers' teaching behavior in lesson preparation and examination system were practiced most of the time.